Performance evaluation of composite asphalt mixture modified with polyethylene and nanosilica - Bala, N. (IAEME Publication, 2017)
In this study, the influence of polymer and nanosilica on performance enhancement of asphalt mixtures was investigated. Asphalt mixtures samples are prepared with polymer nanocomposite modified bitumen incorporating polyethylene and nanosilica at different percentages, the results were compared with control 6 polyethylene polymer modified mixture regarding resistant to draindown, particle loss, and rutting resistance. The study also investigates the application of Response Surface Methodology (RSM) for the prediction of Marshal volumetric properties. Results indicate that, both polyethylene and nanosilica has positive effect on the performance of porous asphalt mixture, they improve rutting resistance significantly, reduces binder draindown and particle loss of porous asphalt mixture, on the other hand, statistical analysis based on RSM shows that a quadratic model developed having a high degree of correlation and predicting ability can be used to predict Marshal volumetric properties of the mixture. © IAEME Publication.